(Why) do we need corporate taxation? - Alfons J. Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2005)
Tax rates on corporate income have considerably come down in the process of tax competition and further pressures are evident. Against this background, the paper discusses possible benefits of corporate income taxation that may be at risk. In particular, the paper surveys the empirical evidence for a backstop function of the corporate income tax that allows preserving individual taxes.
Keywords: H25; 330; tax competition; corporate taxation; Unternehmensbesteuerung; Kapitalertragsteuer; Steuerwettbewerb